PRARANCANGAN PABRIK FENOL FORMALDEHIDA DENGAN KATALIS ASAM (RESIN NOVOLAK) KAPASITAS 25.000 ton/tahun - Novianto, Muhammad Prasojo; Ir. H. Haryanto.A.R, M.S; Emi Erawati, ST, M.Eng (2016)
Novolak resin is one kind of phenol formaldehyde resins in the manufacture using an acid catalyst. Novolak resins has several uses, among others, are used as lacquers, laminating materials, wood adhesives, varnishes and is also used in wall decoration panel. Needs novolak resin itself in Indonesia is still quite high, from 2009 to 2014 every year has increased. Novolak resin plant capacity is 25,000 tons / year, all operating for 330 days, the raw material phenol and formaldehyde, with the ratio of 1: 0.8 and the use of sulfuric acid catalyst. Reaction formation is an exothermic reaction that occurs in the reactor CSTR, liquid-liquid phase, irreversible with the reaction conditions are maintained at a temperature of 95 ° C (isothermal) and a pressure of 1 atm. Novolak resin factory with a capacity of 25,000 tonnes / year of phenol requires raw materials as much as 2419.603 kg / hour, formaldehyde as much as 768.041 kg / hour and sulfuric acid catalyst as much as 173.184 kg / hour. This novolak resin plant needs water as much as 34476.64 kg / h obtained from the river. Saturated steam needs as much as 4298.467 kg / h obtained from the boiler with diesel fuel as much as 0.3747 m3 / h. While electricity obtained from the PLN and a capacity of 3500 KW generator as a backup, with as much fuel as 344,139kg / h. Compressed air needs as much as 56.0736 m3 / h. The factory is planned to be established in the industry Gresik, East Java, with a land area of 15,000 m2 and the number of employees 139 people. From the analysis of the economic, novolak resin plant requires capital of US $ 31,226,814.88 fixed and working capital of US $ 11,277,436.33. Profit before tax of US $ 12,153,334.21 / th. Profits after tax of 9,722,667.37 / year. The feasibility analysis is a result that Percent Return On Investment (ROI) before taxes by 39% and after tax of 31%. Pay Out Time (POT) before tax of 2.04 years, while after tax of 2.43 years. Break Even Point (BEP) at 47% capacity, and Shut Down Point (SDP) at 29% capacity. Discounted Cash Flow (DCF) by 43%. Based on the data above, the novolak resin plant is quite interesting to be established. Keywords: Phenol, Formaldehyde, Sulfuric Acid